Design, development and construction of a new medical wrist rehabilitation device: A project review - Seabra, Eurico (2019)
This paper reviews in detail the design and development procedures for the construction of medical device for the rehabilitation of the wrist. The construction of the actual prototype was carried out with off-the-shelf components. The objective was to develop a functional and low cost device. The system is divided in two main components, one for the rehabilitation of the wrist and the other one to perform proprioception exercises, providing relaxation of the patient’s pain due to injuries on the wrist. All the hardware is assembled in one portable support, capable to make vertical and horizontal adjustments. Both systems are fully controlled through a software specially developed to be used by physiotherapists and patients, allowing also the registration of the rehabilitation evolution.